2016
DOI: 10.1080/02755947.2016.1165764
|View full text |Cite
|
Sign up to set email alerts
|

Mode Effect and Response Rate Issues in Mixed‐Mode Survey Research: Implications for Recreational Fisheries Management

Abstract: While the social, economic, and ecological impact of recreational fisheries is well established, the inherent diversity of both fisheries resources and resource users, particularly anglers, continues to present a challenge for management agencies. To better understand the diversity of recreational anglers, agencies often utilize survey methods to collect data on angler characteristics and preferences. However, obtaining necessary and representative data is becoming more challenging, exacerbated by declining re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 45 publications
4
16
0
Order By: Relevance
“…had an incomplete sample frame, as has been reported elsewhere (e.g., Gigliotti and Dietsch 2014;Zarauz et al 2015;Wallen et al 2016). The cost advantage of the e-mail survey makes it an attractive alternative (McCormick et al 2015); therefore, it is important to explore the reasons for its poor performance before dismissing it as an unsuitable mode (Gigliotti and Dietsch 2014).…”
mentioning
confidence: 95%
See 3 more Smart Citations
“…had an incomplete sample frame, as has been reported elsewhere (e.g., Gigliotti and Dietsch 2014;Zarauz et al 2015;Wallen et al 2016). The cost advantage of the e-mail survey makes it an attractive alternative (McCormick et al 2015); therefore, it is important to explore the reasons for its poor performance before dismissing it as an unsuitable mode (Gigliotti and Dietsch 2014).…”
mentioning
confidence: 95%
“…Obvious considerations pertaining to survey mode include its effect on administration cost and how to harness the distinctive advantages provided by different modes (e.g., fast turnaround time for e-mail surveys; De Leeuw 2005; Buelens and van den Brakel 2015). However, a less-obvious and often-overlooked consideration is the fact that survey mode can potentially prompt varied responses from survey participants and introduce a mode-effect bias (Vannieuwenhuyze and Loosveldt 2013;Wallen et al 2016). Mode-effect is a type of measurement error (Vannieuwenhuyze et al 2010;Dillman et al 2014) and has been shown to have a serious effect on population estimates (Laborde et al 2014;Zarauz et al 2015).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Future studies of angler preferences may benefit from an electronic response option or mixed‐mode approach that could mitigate age bias (Wallen et al. ). Eliminating any potential age bias may be valuable in identifying age‐related differences in preference that may be the result of recent widespread changes in Walleye, Largemouth Bass, and Bluegill fisheries (Hansen et al.…”
Section: Discussionmentioning
confidence: 99%